NAVIGATING THE DIGITAL LANDSCAPE: AN ANALYSIS OF DIGITAL COMPETENCY OF SECONDARY SCHOOL STUDENTS - Neog, Abinash; Erigala, Ashok Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The process of digitalization is applying now a days in almost all aspects of human society. As fast as the process of digitalization is growing the concept of digital competency is also getting importance day by day. During the period of Covid-19 also, digital education has become the major alternative to continue educational activities through the utilization of digital tools and technologies, online learning platforms etc and which is still continuing in the field of education. This study aims to investigate the digital competency level among the students of secondary school of Kamrup district of Assam. The study was conducted on 200 secondary students of class 10 selected by using stratified random sampling technique. For the purpose of collecting data, a self-constructed Digital Competency test was used. Different descriptive and inferential statistics like mean, t-test, standard deviation etc. were applied for analysing the collected data in SPSS software. It was found in the present study that higher percentage of pupils (72.5%) have average digital competency level. Likewise, significant difference in secondary school students’ digital competency with regard to gender, management of school and locality of the school was also identified.